Evaluation of multipactor thresholds for coaxial lines subject to surface conditioning for the WEST ion cyclotron antenna - Al Hajj Sleiman, Eva; Hillairet, Julien; Belhaj, Mohamed; Dadouch, Sarah (Fusion engineering and design, 2022)
Multipactor voltage threshold charts and scaling laws for 30Ω circular coaxial geometries, relevant to the WEST Ion Cyclotron Resonance Heating antennas, are reproduced using a developed multipactor decision-making algorithm relying on Spark-3D electron time-evolution data. The developed methodology is validated by comparing the simulated multipactor powers to the measured multipactor power thresholds, for a 50Ω coaxial geometry. The effects of the conditioning, for a WEST antenna-relevant surface sample, on the total electron emission yield and surface properties are studied. The consequences of the conditioning phase on the multipactor voltage thresholds for coaxial transmission lines of 30Ω and 50Ω characteristic impedance are also highlighted. It is shown that preliminary baking and conditioning suppress or reduce the range in which multipactor can be triggered. •Development of an algorithm based on Spark3D to predict the multipactor bounds.•Compare measured multipactor thresholds to simulated ones, and reproduce scaling laws.•Determine multipactor bounds for 50Ω and 30Ω coaxial cables for WEST relevant conditions.•Study baking and conditioning effects on material properties and on multipactor thresholds.